Genetic Determinants of Survival in Parkinson's Disease in the Asian Population. Issue 8 (26th May 2022) - Li, Chunyu; Hou, Yanbing; Ou, Ruwei; Gu, Xiaojing; Chen, Yongping; Zhang, Lingyu; Liu, Kuncheng; Lin, Junyu; Cao, Bei; Wei, Qianqian; Chen, Xueping; Song, Wei; et al.
Abstract: Background: Patients with Parkinson's disease (PD) have reduced life expectancy compared to the general population. Genetic variation was shown to play a role in the heterogeneity of survival for patients with PD, although the underlying genetic background remains poorly studied. Objective: The aim was to explore the genetic determinants influencing the survival of PD. Methods: We performed a genome‐wide association analysis using a Cox proportional hazards model in a longitudinal cohort of 1080 Chinese patients with PD. Furthermore, we built a clinical‐genetic model to predict the survival of patients using clinical variables combined with polygenic risk score (PRS) of survival of PD. Results: The cohort was followed up for an average of 7.13 years, with 85 incidents of death. One locus rs12628329 ( RPL3 ) was significantly associated with reduced survival time by ~10.8 months ( P  = 2.72E‐08, β = 1.79, standard error = 0.32). Functional exploration suggested this variant could upregulate the expression of RPL3 and induce apoptosis and cell death. In addition, adding PRS of survival in the prediction model substantially improved survival predictability (concordance index [Cindex]: 0.936) compared with the clinical model (Cindex: 0.860). Conclusions: These findings improve the current understanding of the genetic cause of survival of PD and provide a novel target RPL3 for further research on PD pathogenesis and potential therapeutic options. Our results also demonstrate the potential utility of PRS of survival in identifying patients with shorter survival and providing personalized clinical monitoring and treatment. © 2022 International Parkinson and Movement Disorder Society.